Frequency of Hepatic Encephalopathy (HE) among Hepatitis Patients at Mardan Medical Complex, Mardan - Muhammad Bilal, Sajid Ali, Sajjad Mohammad, Mushtaq Ahmad, Amanullah, Syed Luqman Shuaib, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Hepatic encephalopathy (HE) represents severe neuropsychiatric condition of acute and chronic liver disease. Approximately 70% HE found in patients already suffering from liver cirrhosis. The aim of this study was to find the risk factors for developing Hepatic Encephalopathy in patients suffering from Chronic liver disease. Materials and Methods: This descriptive study was conducted in Mardan medical complex in four months duration. Data was collected from one hundred patients using non-probability sampling technique. All the data were analyzed through statistical software, JMP, 10.0 SAS, USA. Results: This study reports the frequency of HE among 100 hepatitis patients with mean age 55±9years. Out of these patients, 58% were males and 42% females. In our study, infection was the main precipitating factor found in most of the patients examined, followed by spontaneous bacterial peritonitis (20% patients), constipation (18% patients), GI bleeding (13% patients), and electrolyte imbalance such as hypokelmia (6% patients) and hypernatremia (3% patients). Conclusion: It is concluded that HE is more common in male patients than female. The risk of HE can be minimized by providing good hygienic conditions and germs free food in hospital.